Additional Screening and Treatment of Malaria During Pregnancy Provides Further Protection Against Malaria and Nonmalarial Fevers During the First Year of Life. (15th March 2018) - Natama, Hamtandi Magloire; Rovira-Vallbona, Eduard; Sorgho, Hermann; Somé, M Athanase; Traoré-Coulibaly, Maminata; Scott, Susana; Zango, Serge Henri; Sawadogo, Ousséni; Zongo, Sibiri Claude; Valéa, Innocent; Mens, Petra F; Schallig, Henk D F H; et al.
Abstract : This study examined the potential benefits of malaria in pregnancy preventive strategies in infants and showed, that enhanced screening and treatment, in addition to standard intermittent preventive treatment with sulfadoxine-pyrimethamine, may provide additional protection against malaria and nonmalarial fevers in early infancy. Abstract: Background: Although consensus exists that malaria in pregnancy (MiP) increases the risk of malaria in infancy, and eventually nonmalarial fevers (NMFs), there is a lack of conclusive evidence of benefits of MiP preventive strategies in infants. Methods: In Burkina Faso, a birth cohort study was nested to a clinical trial assessing the effectiveness of a community-based scheduled screening and treatment of malaria in combination with intermittent preventive treatment with sulfadoxine-pyrimethamine (CSST/IPTp-SP) to prevent placental malaria. Clinical episodes and asymptomatic infections were monitored over 1 year of follow-up to compare the effect of CSST/IPTp-SP and standard IPTp-SP on malaria and NMFs. Results: Infants born during low-transmission season from mothers receiving CSST/IPTp-SP had a 26% decreased risk of experiencing a first clinical episode (hazard ratio, 0.74 [95% confidence interval, .55–0.99]; P = .047). CSST/IPTp-SP interacted with birth season and gravidity to reduce the incidence of NMFs. No significant effects of CSST/IPTp-SP on the incidence of clinical episodes, parasite density, and Plasmodium falciparum infections were observed. Conclusions: Our findings indicate that CSST/IPTp-SP strategy may provide additional protection against both malaria and NMFs in infants during the first year of life, and suggest that malaria control interventions during pregnancy could have long-term benefits in infants.